2012
DOI: 10.4314/wsa.v35i1.76653
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen dynamics in land cleared of alien vegetation (<i>Acacia saligna</i>) and impacts on groundwater at Riverlands Nature Reserve (Western Cape, South Africa)

Abstract: Woody invading alien plants, many of which are nitrogen-fixing legumes (Fabaceae family), are currently cleared in South African catchments to reduce water loss and preserve streamflow, and for the restoration of the ecosystem. This study tested the hypothesis that clearing invasive alien vegetation may disturb the vegetation-micro-organism-soil N cycling system by producing a large once-off input of fresh tree litterfall rich in N and by eliminating a large N sink. Three experimental plots were established at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…In our results, it is surprising that Acacia species did not increase nitrogen concentrations in the topsoil, which can suggest strong leaching from top soil to deeper layers ( Figures S6 and S7). This might affect groundwater as strong NOx contamination has been found in catchments afforested with Acacia saligna (Jovanovic et al, 2009), so large restoration programs with these species should take into account long-term negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…In our results, it is surprising that Acacia species did not increase nitrogen concentrations in the topsoil, which can suggest strong leaching from top soil to deeper layers ( Figures S6 and S7). This might affect groundwater as strong NOx contamination has been found in catchments afforested with Acacia saligna (Jovanovic et al, 2009), so large restoration programs with these species should take into account long-term negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found a low N 6 years after clearing compared to the reference invaded and non-invaded areas. The differences are most likely a result of high N losses in the cleared area (Stock & Lewis 1986;Witkowski 1991;Malcolm et al 2008;Jovanovic et al 2009;Staska et al 2014). It is worth noting that low N in the cleared area compared to the invaded and non-invaded areas were not standard across all study sites.…”
Section: Legacy Effects Of Acacia Saligna On Soil Characteristicsmentioning
confidence: 95%
“…The differences are most likely a result of high N losses in the cleared area (Stock & Lewis 1986;Witkowski 1991;Malcolm et al 2008;Jovanovic et al 2009;Staska et al 2014). The differences are most likely a result of high N losses in the cleared area (Stock & Lewis 1986;Witkowski 1991;Malcolm et al 2008;Jovanovic et al 2009;Staska et al 2014).…”
Section: Legacy Effects Of Acacia Saligna On Soil Characteristicsmentioning
confidence: 98%
“…Soils were collected using a soil auger at a depth of 10 cm after the removal of the overlaying debris. Collection of soils at the above mentioned depth was based on results by Jovanovic et al (2009) who reported that soil nutrients were represented at a depth of 0 -5 cm underneath Acacia sites. After soil collection, soil nutrient analyses, pH, soil resistivity, gravimetric soil moisture and soil repellency were assessed under laboratory condition at Rhodes University in Grahamstown.…”
Section: Site Selectionmentioning
confidence: 99%